VARIABILITY FOR LEAF BLIGHT RESISTANCE IN INDIAN SPRING WHEAT (TRITICUM AESTIVUM) GERMPLASM - PREM KUMAR; RAM DHARI; JITENDRA KUMAR; JAI SINGH (The Bioscan, 2015)
The present investigation on wheat was conducted during the Rabi season 2008-09 with the objective to study variability for leaf blight resistance and to find out the distribution of resistance across various plant height, test weight and days to maturity groups. Seeds of 147 diverse bread wheat (Triticum aestivum) genotypes were sown by following the Lattice Design (7×7) and in two rows of two meter length of each genotype. The field was highly fertilized and frequently irrigated to provide a congenial environment for the development of the leaf blight disease. Observations based on 0-9 scale were shown that a wide variability was observed for resistance to leaf blight in the wheat lines screened in one year of testing based on maximum leaf score.AUDPC value varies from the 92.6 to 123.5 across the resistant lines. Line K0810 shows least value, while PBW 640 shows highest value among the resistant lines. Most of the wheat lines showed moderately susceptible reaction. But, differential reactions was also observed in some lines, thus the differential reaction of leaf blight severity in some of the genotypes supported the idea of independent gene control.